«The self, in the experiencing of itself, is the primal reality». Subjectivity and factical life in the early Heidegger’s thought (Nóema, 2012)
This article makes explicit and clarifies the categories with which the early Heidegger reformulates the traditional seat of subjectivity, focusing in particular on life’s enactive dimension. In the Heideggerian perspective, the question on the human being as well as the philosophical questioning in general take shape coming from and insisting on radical historicity, the original doorway to factical life experience.
Keywords: Early Heidegger; subjectivity; enactment; historicity